1993
DOI: 10.1007/bf00277066
|View full text |Cite
|
Sign up to set email alerts
|

Extent of polyteny in the pericentric heterochromatin of polytene chromosomes of pseudonurse cells of otu (ovarian tumor) mutants of Drosophila melanogaster

Abstract: In the polytene nuclei of germ-line cells (ovarian pseudonurse cells) of Drosophila melanogaster females mutant for otu11 (ovarian tumor), the pericentric heterochromatin is much more abundant than in somatic salivary gland cells. This is due to the degree of heterochromatin compaction (and consequently the level of underreplication) being lower in the nurse cells than in the salivary gland cells. The lower level of compaction probably results in a very low degree of position effect gene inactivation in the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Nurse cell chromosomes that fail to disperse are also observed in certain alleles of ovarian tumor (otu) (King et al, 1981;King and Storto, 1988;Heino, 1989;Mal'ceva and Zhimulev, 1993;Heino, 1994;Mal'ceva et al, 1995). otu produces two protein isoforms, Otu98 and Otu104, by alternative splicing of a 126 bp exon.…”
Section: The Ovarian Tumor Gene Can Rescue the Nurse Cell Nuclear Mormentioning
confidence: 99%
“…Nurse cell chromosomes that fail to disperse are also observed in certain alleles of ovarian tumor (otu) (King et al, 1981;King and Storto, 1988;Heino, 1989;Mal'ceva and Zhimulev, 1993;Heino, 1994;Mal'ceva et al, 1995). otu produces two protein isoforms, Otu98 and Otu104, by alternative splicing of a 126 bp exon.…”
Section: The Ovarian Tumor Gene Can Rescue the Nurse Cell Nuclear Mormentioning
confidence: 99%
“…Our observations are also in line with the results of Hammond and Laird (1985), who demonstrated that during the last endocycle, the regions underreplicated at earlier stages undergo complete replication. This, as well as partial polytenization of pericentric heterochromatin (Mal'ceva and Zhimulev 1993) can be attributed to its earlier replication in NCs as compared to SG polytene chromosomes. However, we must underline that early replication results in only partial polytenization of heterochomatin, with its considerable fraction remaining underreplicated.…”
Section: Discussionmentioning
confidence: 93%
“…Detailed morphology analysis of NC chromosomes from otu mutants indicated that their banding pattern was very similar, yet not entirely identical to that of SG polytene chromosomes (Heino 1989;Mal'ceva et al 1995;. Notably, pericentric heterochromatin is polytenized in otu NCs significantly more than in SG polytene chromosomes and may form structures with reproducible banding pattern (Mal'ceva and Zhimulev 1993;Koryakov et al 1996;1999;. Moreover, the degree of DNA underreplication and hence the frequency of chromosome breaks are much lower in intercalary heterochromatin regions of NC polytene chromosomes vs those of SGs (Mal'ceva et al 1995;Koryakov et al 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Pericentric heterochromatin is almost completely underreplicated in polytene chromosomes of Drosophila (Rudkin, 1965;Berendes and Keyl, 1967;Mulder et al, 1968). Unexpectedly, in otu mutant NC chromosomes, blocks of banded material were present in the heterochromatin region (Mal'ceva and Zhimulev, 1993). In SG chromosomes of SuUR mutants, a reproducible banding pattern appears in the pericentric region of chromosome 3 in place of small lumps of unstructured heterochromatin (Belyaeva et al, 1998;Semeshin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In D. melanogaster, mutation otu causes formation of polytene chromosomes in NCs (King et al, 1981), which show greater polytenization of heterochromatic sequences than in SGs (Mal'ceva and Zhimulev, 1993;Koryakov et al, 1996).…”
mentioning
confidence: 99%